Factors Influencing the Private Involvement in Urban Rail Public-Private Partnership Projects in China (Construction Economics and Building, 2017)
Private investors have been encouraged to participate in the development and operation of urban rail projects in China through Public-Private Partnerships (PPPs), given the fact that subnational governments are suffering from urgent development demands and severe fiscal pressure. However, there is no formal assessment to determine the private involvement in a PPP project. This problem is particularly critical in the sector of urban rail, in which the huge investment cannot rely on the private sector alone. This study hence aimed to uncover and identify the influencing factors. Multiple research methods, including content analysis, case study and focus group discussion were adopted to achieve the research purpose. Seven types of influencing factors were identified, including project financial model, government fiscal commitment, risk allocation, public accountability, efficiency considerations, policy and regulations, and organisational marketing strategies. The findings add to the current knowledge base by uncovering the drivers behind private involvement in a PPP project. They are also beneficial for industry practitioners as a basis/checklist to determine the private involvement.